1992
DOI: 10.3354/meps083075
|View full text |Cite
|
Sign up to set email alerts
|

The micronucleus test: temporal pattern of baseline frequency in Mytilus galloprovincialis

Abstract: ABSTRACT. The base-line frequency of micronucleated cells was measured in g111 tissue of Mytilus galloprov~nc~ahs Lmk. from 2 ~Mediterranean areas (northern Tyrrhenian and northern Adriatic Seas), and turned out to be a function of water temperature and age of the animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…Though baseline frequency of MN depends on variety of biotic and abiotic factors (Brunetti et al, 1988), it can be assumed that higher water temperature in the offshore areas of the Baltic and the North Sea affects mitotic activity and MN formation in fish. Micronuclei are formed during cell division, and the mitotic activity of poikilotherm organisms very largely depends on water temperature (Brunetti et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Though baseline frequency of MN depends on variety of biotic and abiotic factors (Brunetti et al, 1988), it can be assumed that higher water temperature in the offshore areas of the Baltic and the North Sea affects mitotic activity and MN formation in fish. Micronuclei are formed during cell division, and the mitotic activity of poikilotherm organisms very largely depends on water temperature (Brunetti et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Although pollutants can cause genetic damage in M. edulis (e.g. Brunetti et al 1992), Sirover & Loeb (1976 and Nacci et al (1992) indicate that copper has limited genotoxicity. Pre-exposure to small amounts of copper can increase the resistance of adult mussels to higher concentrations (Davenport & Manley 1978, Roesijadi & Fellingham 1987, probably by stimulating the synthesis of metallothionein (Viarengo et al 1980, Viarengo 1989.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Brunetti et al (1992) suggested a considerable influence of temperature on MN frequency. Analysing the current temporal pattern of ENA frequency is not discernible a clear influence of temperature on its expression.…”
Section: Ena Frequencymentioning
confidence: 97%